Organizing for Social and Institutional Change in Response to Disruption, Division, and Displacement: Introduction to the Special Issue. Issue 10 (October 2022) - Creed, W. E. Douglas; Gray, Barbara; Höllerer, Markus A.; Karam, Charlotte M.; Reay, Trish
In this editorial for our Special Issue, we focus on ways to better understand the role of organizations, organizing, and the organized during social and institutional change in response to disruption, division, and displacement . The papers in this Special Issue provide important insights into the hardships and heartache arising from social disruption, division, and displacement; in addition, they provide glimpses into potential ways of moving forward. To set the stage, we develop a framework building on extant literature that highlights several analytic approaches to understanding the consequences of eroding, or inadequate, institutions, the challenges of building anew when the status quo is destroyed, and what such novel and complex realities entail for organizational analysis. We offer a temporal view of responses to disruption, division, and displacement that draws on the papers in this Special Issue to identify and explain potential risks and challenges that arise at different points in time. To conclude, we provide a short summary of each paper, and call for a reinvigorated research agenda that goes beyond the excellent work featured here by broadening and deepening our focus on approaches to organizing that expressly address disruption, division, and displacement.